The European Restructuring Directive and stays on creditor enforcement actions. (2nd August 2021) - McCormack, Gerard
Abstract: The European Restructuring Directive is Europe's answer to Chapter 11 of the US Bankruptcy Code. Under the Directive, debtors will have access to early warning tools that enable them to detect a deteriorating business and this should lead to more restructurings at an early stage. The debtor will benefit from a time‐limited 'breathing space' from enforcement action in order to facilitate negotiations on a restructuring plan. This article analyses in critical detail the stay or moratorium on actions against the debtor during the restructuring process. The stay is a fundamental part of the Directive. The paper highlights the importance of the stay and locates the stay in the context of the Directive and also in the light of the international parallels found in the US Bankruptcy Code and the UNCITRAL Legislative Guide on Insolvency Law.